GEOCHEMICAL ANALYSIS OF SILICEOUS SEDIMENTS FROM VASILIKA, NORTHERN GREECE - Karageorgiou, S.; Vavelidis, M.; Andreou, S.; Melfos, V. (Bulletin of the Geological Society of Greece, 2016)
The present paper presents new mineralogical and geochemical data of the siliceous sediments from the region of Vasilika in northern Greece. The studied material consists of reddish and brownish cherts and jaspers containing mostly microcrystalline quartz and Fe-oxides. Chemical analysis has been carried out, including the identification of major oxides, trace elements and REE, in order to determine their geotectonic affinity based on the correlation of immobile trace element distribution. The geochemical features combined with the mineralogical composition of these siliceous sediments indicate that they were formed as the result of a hydrothermal circulating convection system near a mid-ocean ridge. Rare earth elements (REE) are regarded as the most reliable immobile elemental components in the complex geological process of the sedimentary cycle because they are relatively stable during post-depositional processes such as diagenesis, alteration and weathering. In addition Ce anomaly can help to establish the marine environment in which cherts were formed